1985
DOI: 10.1080/10934528509375267
|View full text |Cite
|
Sign up to set email alerts
|

The response of tomato plants to simulated landfill gas mixtures

Abstract: The roots of tomato plants were fumigated with simulated refuse-generated gas mixtures at levels of methane (CH 4 ), carbon dioxide (CO 2 ), and oxygen (O 2 ) previously measured in the atmospheres of landfill cover soils associated with poor growth or death of plants (5). A concentration of 18% CO 2 or greater, exceeded in almost 30% of thirty-two landfills examined throughout the United States, caused reduced growth and visible symptoms on tomato after 1 wk, regardless of O 2 level. Doubling the CO 2 level t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Vegetation damage at or nearby to such sites is well documented in the literature Leone et al, 1977;Leone and Flower, 1982;Gilman, 1980;Gilman et al, 1981Gilman et al, , 1982Gilman et al, , 1985Arthur et al, 1985). The damage occurs primarily due to oxygen deficiency in the root zone resulting from a direct displacement of oxygen by landfill gas.…”
Section:  mentioning
confidence: 90%
“…Vegetation damage at or nearby to such sites is well documented in the literature Leone et al, 1977;Leone and Flower, 1982;Gilman, 1980;Gilman et al, 1981Gilman et al, , 1982Gilman et al, , 1985Arthur et al, 1985). The damage occurs primarily due to oxygen deficiency in the root zone resulting from a direct displacement of oxygen by landfill gas.…”
Section:  mentioning
confidence: 90%
“…Methane oxidising activity, with a decrease in soil O 2 and an increase in soil biomass, has been demonstrated around leaks in natural gas pipes (Adams and Ellis, 1960;Adamse et al, 1972). Arthur et al (1985), Gilman et al (1982) and Hoeks (1972b) found that elevated CH 4 concentrations were associated with depleted O 2 of between 0 and 12% and elevated CO 2 concentrations of up to 35% in the soil atmosphere.…”
Section: Effect Of Bacterial Oxidationmentioning
confidence: 96%
“…Methane per se has not been shown to be toxic to plants, and aerial contact of plants with natural gas has not been shown to have any harmful effects- Gustafson (1944) found that a range of species showed no signs of altered growth or epinasty (a change in the angle between the petiole and the stem) when exposed to concentrations of 2% CH 4 in air for up to 21 days. It has been suggested that the main damaging effect on plant growth of natural gas leaking from pipelines into the soil is due to the displacement of soil O 2 (Arthur et al, 1985;Gilman et al, 1982;Hoeks, 1972b;Smith, 2002) and this effect may be compounded by the oxidation of leaking CH 4 by methanotrophic bacteria that utilise the CH 4 present in natural gas as a carbon-based energy source (Hanson and Hanson, 1996). However, Meissner et al (1999) suggest that the effect may be more complicated than simple displacement of O 2 by the CH 4 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies carried out at sites of naturally occurring CO 2 springs / vents and or volcanic sites have shown that elevated soil CO 2 concentrations reduce plant growth, disrupt plant photosynthesis, inhibit root respiration mainly due to sever dearth of soil O 2 levels, and even kill the vegetation (Cook et al, 1998;Macek et al, 2005;Miglietta et al, 1998;Pfanz et al, 2007;Vartapetian & Jackson, 1997;Vodnik et al, 2006). Previous studies on leaking CH 4 gas have also caused the same stress symptoms on above-ground vegetation as both CO 2 and CH 4 gases displace O 2 gas from the soil (Arthur et al, 1985;Hoeks, 1972;Smith et al, 2005;Smith, 2002) thus depriving the plant roots off O 2 for respiration, which in turn affects other plant functions viz., water and nutrient uptake, evapotranspiration, photosynthesis and ultimately plant growth. In fact, Adamse et al (1972) suggested that for the proper functioning of a healthy root system, a minimum soil O 2 concentration of 12-14% is required, whereas at ASGARD site in the gassed plots this was not the case.…”
Section: Effect Of Co 2 Gassing On Pasture Grass Stress Symptoms and mentioning
confidence: 78%